Accuracy of radiographic assessment of interproximal bone loss in intrabony defects using linear measurements - Eickholz, Peter; Hausmann, Ernest (European journal of oral sciences, 2000)
The aim of the present study was to examine the accuracy of linear measurements on radiographs of interproximal bone loss in intrabony defects utilizing the gold standard of surgical measurements. In 22 patients with untreated advanced periodontal disease, 33 standardized radiographs were taken presurgically.
First published: 25 December 2001
Elektronische Reproduktion der Druck-Ausgabe
Gesehen am 19.02.2021